2022
DOI: 10.3390/atmos13060907
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Urban Morphological Parameters in the Spatiotemporal Distribution of PM10 and NO2, Taking Dalian as an Example

Abstract: Recently, air quality has become a hot topic due to its profound impact on the quality of the human living environment. This paper selects the tourist city of Dalian as the research object. The concentration and spatial distribution of PM10 and NO2 in the main urban area were analyzed during the peak tourist seasons in summer and winter. Simulations were used to explore the spatial and temporal variation patterns of PM10 and NO2, combining building and road density at different scales to reveal the coupling re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…A high density of buildings has a significant effect on urban air quality in terms of blocking pollutant dispersion when pollutants accumulate in an area, resulting in poor air quality. Su et al [18] found that pollutant concentrations in economically developed areas were greater than those in rural areas. Moreover, these concentrations were associated with the densities of main roads and buildings.…”
Section: Introductionmentioning
confidence: 99%
“…A high density of buildings has a significant effect on urban air quality in terms of blocking pollutant dispersion when pollutants accumulate in an area, resulting in poor air quality. Su et al [18] found that pollutant concentrations in economically developed areas were greater than those in rural areas. Moreover, these concentrations were associated with the densities of main roads and buildings.…”
Section: Introductionmentioning
confidence: 99%
“…The land layout is no less critical for air pollution. First of all, the density of buildings adversely affects air quality [ 30 ]. It has also been observed that on flat terrain, it is only sometimes possible to determine the influence of location on PM concentration.…”
Section: Introductionmentioning
confidence: 99%